Legal Aid for Effective Victim Legal Representation in Kenya’s Post-Election Violence: Lessons from the International Criminal Court - Khamala, Charles A. (International Journal of Criminology and Sociology, 2022)
The International Criminal Court’s legal aid scheme pays court-appointed victims’ lawyers. Yet, whether ICC or domestic legal proceedings can provide better victim satisfaction goes beyond the question of whether external or internal legal representation is more effective in protecting victims’ rights. In circumstances where guilt is difficult to prove, as in the ICC’s Kenya cases, victims’ interests may be better satisfied by pursuing compensation from local courts. This paper therefore argues that post-election violence victims’ interests may be satisfied by legal aid to support domestic compensation claims. Although numerous victims participated in the Kenya cases, non-confirmation of charges against the former Police Commissioner, withdrawal of the Muthaura and Kenyatta case, and declining to conduct reparation hearings after vacating charges in the Ruto and Sang case, culminated in widespread victim dissatisfaction. The paper contrasts the victims’ plight in the Kenya cases with fortunes of victims who participated at the ICC with those of the CAVI Police Shooting case and COVAW Sexual and Gender Based Violence case which effectively proved more satisfying for some victims. The question is whether legal aid for victims’ representatives before domestic courts may enhance the effectiveness of local responses to atrocity crimes. Although the comparatively successful recent domestic suits illustrate advantages of pursuing constitutional-based compensation claims, as opposed to punitive-contingent reparations before the ICC, these test cases require upscaling. Notwithstanding the ‘Kenyan Trial Approach’s’ significant impact on ICC evolution, to vindicate victims’ rights, the Trust Fund for Victims may consider donating to Kenya’s Victim Protection Fund so as to supplement PEV victim compensation. Kenya’s Legal Aid Act requires reforms to support indigent victims, particularly those suffering abuse of power.